Ectrópio palpebral em portador da síndrome de Down e conjuntivite alérgica: Relato de caso - Shiratori, Claudia Akemi; Komatsu, Maria Claudia; Schellini, Silvana Artioli [UNESP]; Cvintal, Tadeu (FapUNIFESP (SciELO), 2007)
This is a case report of a patient with Down's syndrome with an important mechanical ectropion and elongation of the lower lid related to chronic allergic conjunctivitis, besides cataract and keratoconus. The tarsal strip technique and ressection of redundant and thick conjunctiva was the surgical approach chosen for this case. Functional and cosmetic outcomes were considered satisfactory.
Eyelid ectropion in Down's syndrome related to allergic conjunctivitis: Case report
Keywords: Blepharoplasty; Case reports [Publication type]; Conjunctiva/surgery; Conjunctivitis, allergic; Down syndrome; Ectropion; adult; case report; conjunctivitis; ectropion; eyelid reconstruction; human; male; methodology; suturing method; Adult; Conjunctivitis; Down Syndrome; Humans; Male; Suture Techniques